The Effect of Platelet and Mean Platelet Volume Levels on Standard-dose Methylprednisolone Treatment Response in Primary Immune Thrombocytopenia - Emrah KILICASLAN; Murat YILDIRIM; Selim SAYIN; Erdem CEVIK; Meltem AYLI; Muhammet Kursat KAPTAN (Medeniyet Medical Journal)
Objective: Standard-dose methylprednisolone (methyl-Pd) is generally preferred as the first-line treatment in immune thrombocytopenia (ITP) unless there is an urgent indication to increase the platelet value. A significant proportion of patients (around 40%) does not benefit from this treatment. This study investigated whether pretreatment platelet level and other hemogram indices in patients with ITP patients can be used to predict early response to standard-dose methyl-Pd treatment. Methods: Patients who received first-line standard-dose methyl- Pd therapy with the diagnosis of primary ITP were included. Patients were categorized as complete responder (CR), responder (R), and nonresponder (NR) according to the response status obtained within the first 14 days of treatment. The hemogram indices of the CR, R, and NR groups measured at the start of the treatment were compared retrospectively. Results: One hundred forty four patients with ITP were included in the study. The number of patients with NR, R, and CR were 47 (33%), 40 (28%), and 57 (39%), respectively. The mean platelet level of the NR group was lower than responders (R and CR groups) (p=0.002 and p=0.049, respectively). The mean platelet volume (MPV) levels of the NR group were statistically lower than that of the CR group (p=0.018). If MPV ≥10 fL and platelet >12,000/mm³, the probability of an early response with methyl-Pd is higher [sensitivity =98.1% (95% confidence interval (CI) =89.7-99.9%), specificity =45% (95% CI =23.1-68.5%), positive predictive value =82.3% (95% CI =75.7-87.4%), negative predictive value =90% (95% CI =54.9-98.5%)]. Conclusions: Patients with ITP with low platelet and MPV levels were less responsive to standard-dose methyl-Pd treatment. It may be more appropriate to apply more effective treatments to these patients other than standard-dose methyl-Pd alone.